THE FUNDAMENTAL RIGHTS OF CHILDREN DEPRIVED OF LIBERTY INDETENTION CENTRES IN MALAYSIA DURING THE COVID-19 PANDEMIC: A QUALITATIVE STUDY (UUM Journal of Legal Studies, 2023)
The spread of the Covid-19 virus that initially surfaced in China in late 2019 eventually emerged as a global pandemic which adversely affected the worldwide population, including Malaysia. Consequently, the Malaysian government implemented many social and public health measures to help control the spread of Covid-19 in the country. The Covid-19 pandemic affected every level of society in Malaysia, including children who are susceptible to being emotionally, psychologically, and mentally affected due to lockdown measures, school closures, and loss of employment suffered by family members. There is a gap in existing research concerning the impact of Covid-19 on children deprived of liberty in detention centres in Malaysia. Hence, this study aims to identify whether the legal framework in Malaysia adequately protects the rights of children deprived of liberty in detention centres, in line with the international legal framework. A qualitative research design was adopted to explore the issues surrounding the impact of Covid-19 on children in detention centres. Library-based research and semi-structured interviews were carried out with officers from detention centres and the Department of Social Welfare. This research demonstrates that soundpolicies and guidelines and the availability of fully trained staff are essential in meeting the emotional, physical, and mental needs of children in detention centres. This research is significant for policymakers to strengthen the current legal framework in order to afford better protection for children in detention centres, in line with the Ministry of Women, Family and Community Development Policy (2021-2025) as well as the international legal framework.